2021
DOI: 10.3390/medicina57040306
|View full text |Cite
|
Sign up to set email alerts
|

Early Results of Kinesio Taping and Steroid Injections in Elbow Lateral Epicondylitis: A Randomized, Controlled Study

Abstract: Background and objectives: This study prospectively compares early results of Kinesio tape (KT) as an alternative method for the treatment of lateral epicondylitis with those of corticosteroid injection and the rest-and-medication group (RMG). Materials and methods: Among the fifty patients (53 elbows), KT was applied to 20 patients (21 elbows), and corticosteroid injection (CSI) was applied to 15 patients (17 elbows). Fifteen patients were included in the RMG. Patients in the RMG were informed about their con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…The purpose is to relieve the adhesion of elbow tendon tissue, help patients relieve pain symptoms, restore normal joint shape and move freely, and finally achieve the goal of treating both symptoms and root causes [17][18]. The specific mechanism of manipulation is to stimulate the activity of inflammatory factors in local muscles through muscle stretching, thus reducing muscle stiffness, inducing blood vessel repair and reducing muscle oxygen demand during exercise, thus improving muscle cell vitality and enhancing muscle cell activity [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose is to relieve the adhesion of elbow tendon tissue, help patients relieve pain symptoms, restore normal joint shape and move freely, and finally achieve the goal of treating both symptoms and root causes [17][18]. The specific mechanism of manipulation is to stimulate the activity of inflammatory factors in local muscles through muscle stretching, thus reducing muscle stiffness, inducing blood vessel repair and reducing muscle oxygen demand during exercise, thus improving muscle cell vitality and enhancing muscle cell activity [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, 20,[22][23][24][25]28,30,31 a single injection application at the most tender site was performed. Variably, the two to three injection application at different follow-ups and technique of application at different tender sites till the pain-free elbow range of motion was achieved in three studies.…”
Section: Number Of Injections and Techniquementioning
confidence: 99%
“…Lateral elbow tendinopathy resolves within 1 year as told by Cyriax earlier. 6 Erpala et al 24 reported outcomes for a follow-up of 4 weeks where CSI, RMG, and KT were the same.…”
Section: Study Follow-up Duration and Outcomementioning
confidence: 99%
“…pemberian obat-obatan, semuanya efektif dalam hal pengurangan nyeri dan skor fungsional pada akhir minggu ke-2, dan satusatunya pengobatan yang terus efektif sampai minggu ke-4 adalah pada kelompok taping. 4 Kami laporkan laporan kasus efektivitas NMT pada kasus seorang wanita dengan CTS bilateral yang dilakukan NMT selama 2 minggu dengan pemasangan sebanyak tiga kali dan didapatkan perbaikan dari keluhan pasien yang terlihat dari perbaikan skor NRS pasien.…”
Section: Pendahuluanunclassified
“…Studi oleh Erpala dkk, membandingkan hasil antara taping dan injeksi steroid pada epikondilitis siku, didapatkan injeksi steroid, taping, maupun pemberian obatobatan, semuanya efektif dalam hal pengurangan nyeri dan skor fungsional pada akhir minggu ke-2, dan satu-satunya pengobatan yang terus efektif sampai minggu ke-4 adalah pada kelompok taping. 4 Pemberian injeksi kortikosteroid jangka panjang dapat mempengaruhi kemampuan reparatif jaringan, sehingga menunda proses self-limiting dari jaringan dengan mencegah pelepasan sitokin. 8 Selain itu, efek samping seperti infeksi, reaksi alergi, osteonekrosis, ruptur tendon, dan cedera saraf atau tendon harus dipertimbangkan.…”
Section: Pembahasanunclassified